1998
DOI: 10.1046/j.1365-2249.1998.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

C7 deficiency in an Irish family: a deletion defect which is predominant in the Irish

Abstract: Human deficiencies of terminal complement components are known to be associated with increased susceptibility to Neisseria meningitidis infection. Polymorphic DNA marker studies in complement deficient investigations allow identification of haplotypes associated with the deficiency and enable the possible identification of heterozygote carriers of the defect. We report studies of an Irish family in which the index case had suffered recurrent meningococcal disease and was found to be deficient in the seventh co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…This patient also had chronic otitis media that was only partially responsive to medical treatment; S. aureus and Bacteroides faecalis were cultured from middle ear pus (353). Complete deficiencies of C7 have been reported in several cases, and the molecular basis includes mutations at a 3Ј splice acceptor site in intron 1 (125), a mutation at a 5Ј splice donor site of intron 16, several point mutations (124,489), and deletion of part of the gene (326).…”
Section: Inherited Deficiencies Of Complement Activationmentioning
confidence: 99%
“…This patient also had chronic otitis media that was only partially responsive to medical treatment; S. aureus and Bacteroides faecalis were cultured from middle ear pus (353). Complete deficiencies of C7 have been reported in several cases, and the molecular basis includes mutations at a 3Ј splice acceptor site in intron 1 (125), a mutation at a 5Ј splice donor site of intron 16, several point mutations (124,489), and deletion of part of the gene (326).…”
Section: Inherited Deficiencies Of Complement Activationmentioning
confidence: 99%
“…In particular, the recent discovery of the molecular basis of C6 deficiency in the Western Cape, South Africa showed that the defect was associated with a single haplotype in 27 unrelated chromosomes and with variation at single loci in 3 other chromosomes. Also, 7 out of 8 C7-deficient Israeli chromosomes with a common defect share one haplotype (Fernie et al 1997a) and 4 out of 5 C7-deficient Irish with a common defect share a haplotype (Fernie et al 1997a;O'Hara et al 1998). In summary, 38 chromosomes show association and 5 show only minor variations from the common associated haplotypes.…”
Section: Marker Haplotypes and Zygositymentioning
confidence: 99%
“…Six defects, including the one responsible for C7SD in C6/C7SD and as isolated C7D, have been reported previously [65,75,76,78]. At this meeting a further 7 defects were described [63,77], making a total of 13 different known C7 defects.…”
Section: Deficiencies Of C7mentioning
confidence: 91%
“…Nevertheless, C7D can occur with a relatively high frequency in certain populations. A defect at nucleotide position 1135 in exon 9 has been found in eight independent chromosomes in Jews of Moroccan Sephardic descent living in Israel, and an unusual deletion of around 6.8 kbp, including exons 7 and 8, has been found in five independent chromosomes in Ireland [76,78].…”
Section: Deficiencies Of C7mentioning
confidence: 99%